In situ cross-linked nonaqueous polymer electrolyte for zinc-metal polymer batteries and hybrid supercapacitors - Vijayakumar, Vidyanand; Ghosh, Meena; Kurian, Maria; Torris, Arun; Dilwale, Swati; Badiger, V. Manohar; Winter, Martin; Nair, Jijeesh Ravi; Kurungot, Sreekumar (Small, 2020)
This work reports the facile synthesis of nonaqueous zinc-ion conducting polymer electrolyte (ZIP) membranes using an ultraviolet (UV)-light-induced photopolymerization technique, with room temperature (RT) ionic conductivity values in the order of 10(-3)S cm(-1). The ZIP membranes demonstrate excellent physicochemical and electrochemical properties, including an electrochemical stability window of >2.4 V versus Zn|Zn(2+)and dendrite-free plating/stripping processes in symmetric Zn||Zn cells. Besides, a UV-polymerization-assisted in situ process is developed to produce ZIP (abbreviated i-ZIP), which is adopted for the first time to fabricate a nonaqueous zinc-metal polymer battery (ZMPB; VOPO4|i-ZIP|Zn) and zinc-metal hybrid polymer supercapacitor (ZMPS; activated carbon|i-ZIP|Zn) cells. The VOPO(4)cathode employed in ZMPB possesses a layered morphology, exhibiting a high average operating voltage of approximate to 1.2 V. As compared to the conventional polymer cell assembling approach using the ex situ process, the in situ process is simple and it enhances the overall electrochemical performance, which enables the widespread intrusion of ZMPBs and ZMPSs into the application domain. Indeed, considering the promising aspects of the proposed ZIP and its easy processability, this work opens up a new direction for the emergence of the zinc-based energy storage technologies.
Keywords: nonaqueous electrolytes; polymer electrolytes; postlithium batteries; Supercapacitors; zinc-metal batteries

Insights on prussian blue analogue cathode material engineered with polypyrrole surface protection layer for aqueous rechargeable zinc metal battery - Puthiyaveetil, Priyanka Pandinhare; Nair, Aathira; Dilwale, Swati; Kurian, Maria; Joshi, Kavita; Kurungot, Sreekumar (Small, 2024)
One of the key intricacies against using Prussian blue analogues (PBAs) in aqueous batteries is their gradual dissolution in aqueous electrolytes, resulting in inadequate cycling stability. Besides, the rate capability of PBAs is limited due to their poor electrical conductivity. To overcome these challenges, it is essential to tune the physical and chemical properties of PBAs at the nano regime without affecting the inherent charge storage properties, especially at high-voltage operating conditions. Through this work, a strategy is demonstrated to enhance the electrochemical performance of vanadium-based PBA (V-PBA) by surface engineering using a conducting polymer nano-skin (V-PBA/PPy) for aqueous zinc metal batteries. The polypyrrole (PPy) nano-skin over the V-PBA nanoparticles acts as an electron percolation path to ameliorate the poor electronic conductivity of the otherwise pristine V-PBA. Interestingly, the V-PBA with an optimized polypyrrole coating (V-PBA/PPy-2) exhibits an enhanced specific capacity (173 mAh g-1 at 0.10 A g-1) than the pristine V-PBA counterpart (80 mAh g-1) and 85% capacity retention up to 500 cycles. The DFT calculation confirms the synergistic interaction between PPy and V-PBA and the presence of PPy favors the adsorption of Zn.
Keywords: aqueous rechargeable zinc metal battery; DFT; polypyrrole coating; Prussian blue analogue; surface protection layer

Interlayer space engineering-induced pseudocapacitive zinc-ion storage in holey graphene oxide-bearing vertically oriented MoS2 nano-wall array cathode for aqueous rechargeable Zn metal batteries - Babu, Athira; Dilwale, Swati; Kurungot, Sreekumar (Small, 2024)
Transition metal dichalcogenides, particularly MoS2, are acknowledged as a promising cathode material for aqueous rechargeable zinc metal batteries (ARZMBs). Nevertheless, its lack of hydrophilicity, poor electrical conductivity, significant restacking, and restricted interlayer spacing translate into inadequate capacity and rate performance. Herein, the unique porous structure and additional functional groups present in holey graphene oxide (hGO) are taken advantage of to dictate the vertical growth pattern of oxygen-doped MoS2 nanowalls (O-MoS2/NW) over the hGO surface. Compared to conventional graphene oxide (GO), the presence of nano-pores in hGO facilitates the homogeneous dispersion of Mo precursors and provides stronger interaction sites, promoting the uniform vertical alignment of O-MoS2/NW. The synergistic interaction between O-MoS2-NW and hGO translates to enhanced electron conductivity, efficient electrolyte penetration, enhanced interlayer spacing, reduced restacking, and enhanced surface area. As a consequence of precise control of various factors that decide the overall battery performance, a high discharge capacity (227 mAh g(-1) at 100 mA g(-1)) cathode material with significantly lower charge transfer resistance (66 Omega) compared to pristine O-MoS2 (153 Omega) is developed. These findings underscore the potential of hGO as a multifunctional platform for nanoengineering high-performance cathode materials for the next generation of efficient and durable ARZMBs.
Keywords: aqueous rechargeable zinc metal battery; holey graphene oxide; hydrophilicity tuning; interlayer space engineering; oxygen-doped MoS2; transition metal dichalcogenide; vertical nanowall